Analisis Pola Asuh Orang Tua dan Hasil Belajar Siswa Kelas IV SD N Pedurungan Kidul 02 - Viery David Sandika; Eka Sari Setianingsih; Suyitno Suyitno (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The background research is based on the lack of awareness of parents about the importance of providing effective parenting for children which affects student learning outcomes obtained at school. There are several problems found in this study, namely the parenting style applied by students' parents and the learning outcomes obtained by students. This study aims to determine the effect of parenting style on the learning outcomes of fourth grade students of SDN Pedurungan Kidul 02. Based on these problems, the type of research used is descriptive qualitative with a percentage descriptive approach. The research subjects were parents and grade IV students of SDN Pedurungan Kidul 02. Data collection techniques using observation, interviews, questionnaires and documentation. The results of the study, the researcher found three parenting styles applied by the students' parents in accordance with the research focus, namely authoritarian parenting, democratic parenting, and permissive parenting. More democratic parenting is applied by parents, following authoritarian parenting and permissive parenting. Student learning outcomes are satisfactory. It is proven that 47% of students already have excellent learning outcomes and 53% have good learning outcomes. The conclusion of this study, parenting style does not affect student learning outcomes.